1994
DOI: 10.1016/0014-5793(94)00417-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonendothelial‐derived nitric oxide activates the ATP‐sensitive K+ channel of vascular smooth muscle cells

Abstract: To determine whether endogenous nitric oxide (NO) opens the ATP-sensitive K+ channel (KAV channel), we investigated the effect of nonendothelialderived NO on this channel in cultured smooth muscle cells of the porcine coronary artery by the patch-clamp technique. In the cells pretreated with endotoxin, the addition of lo-" M L-arginine generated NO and activated the KATp channel. Activation of this channel was suppressed by pretreatment with 10e3 M NG-methyl-L-arginine or 10m3 M N"-nitro+arginine methyl ester,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 17 publications
4
43
1
1
Order By: Relevance
“…33 However, no significant difference in the vascular responses observed between the diabetic patients treated with diet alone and those treated with sulfonylurea in the current study (data not shown) is consistent with the study by McVeigh et al 34 Another important factor contributing to endothelial dysfunction in diabetes mellitus is reported to be hyperglycemia in vivo. [35][36][37] In the current study, both plasma glucose and HbA1c levels were significantly higher in the diabetic patients than in the control subjects.…”
Section: Discussionsupporting
confidence: 83%
“…33 However, no significant difference in the vascular responses observed between the diabetic patients treated with diet alone and those treated with sulfonylurea in the current study (data not shown) is consistent with the study by McVeigh et al 34 Another important factor contributing to endothelial dysfunction in diabetes mellitus is reported to be hyperglycemia in vivo. [35][36][37] In the current study, both plasma glucose and HbA1c levels were significantly higher in the diabetic patients than in the control subjects.…”
Section: Discussionsupporting
confidence: 83%
“…Relevant to the present study, NO has been reported to activate KATP channels in mammalian vascular smooth muscle (Miyoshi et al, 1994;Murphy and Brayden, 1995), as well as sarcolemmal (Moncada et al, 2000) and mitochondrial channels in ventricular myocytes. The latter investigators used whole-cell recording techniques to show that SNAP activated mitochondrial but not sarcolemmal KATP channels in rabbit ventricular myocytes .…”
Section: Nitric Oxidesupporting
confidence: 72%
“…The cGMPdependent protein kinases may be capable of phosphorylating K ATP channels and priming the channel to offer cardioprotection. 28, 29 Miyoshi et al 7 provided direct evidence that NO enhances K ATP channel activity in vascular smooth muscle cells. Recently, Sasaki et al 30 confirmed this observation by demonstrating direct activation of the mitochondrial K ATP channel with exogenously generated NO in myocytes.…”
Section: No and Intracellular Signalingmentioning
confidence: 99%
“…6 The mediator in opening of the K ATP channel after adenosine-induced protection is not known. Because NO has been proposed to open K ATP channels, 7 we hypothesized that the A 1 AR may mediate this protective effect via an NO-sensitive mechanism. We carried out the present investigation in the isolated mouse and in genetically engineered inducible nitric oxide synthase (iNOS) gene-knockout mice to provide the direct cause-andeffect relationship of iNOS in adenosine-induced delayed cardioprotection.…”
mentioning
confidence: 99%